2020
DOI: 10.3389/fpsyg.2020.613585
|View full text |Cite
|
Sign up to set email alerts
|

School Satisfaction in Immigrant and Chilean Students: The Role of Prejudice and Cultural Self-Efficacy

Abstract: Latin-American immigration has transformed Chilean schools into new multicultural scenarios. Studies about intergroup dynamics among students from different cultural backgrounds and their psychological consequences are still limited in south–south migration contexts. Literature has suggested that intergroup relations influence students’ satisfaction with school, and they could be improved by the development of competences to cope with cultural differences. This study aims to verify if cultural self-efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
(165 reference statements)
0
1
0
2
Order By: Relevance
“…Por otra parte, se observa una baja percepción de prejuicio afectivo hacia los inmigrantes latinoamericanos por parte de los adolescentes, lo que también ha sido observado en otros estudios con muestras de adolescentes chilenos (Mera-Lemp, Bilbao & Basabe, 2020). En cuanto a la percepción de autoeficacia cultural general, los adolescentes se sienten moderadamente capaces de interactuar exitosamente con miembros de otros grupos culturales.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por otra parte, se observa una baja percepción de prejuicio afectivo hacia los inmigrantes latinoamericanos por parte de los adolescentes, lo que también ha sido observado en otros estudios con muestras de adolescentes chilenos (Mera-Lemp, Bilbao & Basabe, 2020). En cuanto a la percepción de autoeficacia cultural general, los adolescentes se sienten moderadamente capaces de interactuar exitosamente con miembros de otros grupos culturales.…”
Section: Discussionunclassified
“…En cuanto a la percepción de autoeficacia cultural general, los adolescentes se sienten moderadamente capaces de interactuar exitosamente con miembros de otros grupos culturales. La dimensión de autoeficacia para comprender otros estilos de vida obtiene el puntaje mayor, seguido por la dimensión de autoeficacia para relacionarse con otras culturas, y la dimensión de autoeficacia para procesar información de otras culturas, que obtuvo el menor puntaje, similar a lo observado en otros estudios en adolescentes chilenos (Mera-Lemp, Bilbao & Basabe, 2020). Asimismo, el nivel de bienestar de los participantes es adecuado.…”
Section: Discussionunclassified
“…Du et al (2015) studied internal Chinese migrants and concluded that increased cultural self-e cacy under a collectivist cultural orientation could effectively reduce depression [32]. Another previous study demonstrated that increasing cultural self-e cacy could reduce prejudice among international students and thus increase school satisfaction [33]. In summary, cultural self-e cacy is a positive emotion that can positively contribute to social adaptation.…”
Section: Cultural Self-e Cacymentioning
confidence: 99%